A Numerical Study of Thermal Stress in Nafion and PTFE Membranes of Fuel Cell - N S, Sudeep; Bekal, Sudesh (International Journal of Engineering and Technology, 2026)
Membrane is necessarily required for the chemical reaction in fuel cell. Periodic variation in the temperature generates thermal stress during the process affecting the performance of membrane. In this paper, thermal stress produced in fuel cell having Nafion and PTFE membrane and its effect on proton and water transport are studied by simulation. For the purpose governing equations developed by other researchers were used for modelling and simulation. From the study, the use of PTFE membrane over Nafion reduces thermal stress by 44%.